-x+9=69+5x

Simple and best practice solution for -x+9=69+5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x+9=69+5x equation:


Simplifying
-1x + 9 = 69 + 5x

Reorder the terms:
9 + -1x = 69 + 5x

Solving
9 + -1x = 69 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
9 + -1x + -5x = 69 + 5x + -5x

Combine like terms: -1x + -5x = -6x
9 + -6x = 69 + 5x + -5x

Combine like terms: 5x + -5x = 0
9 + -6x = 69 + 0
9 + -6x = 69

Add '-9' to each side of the equation.
9 + -9 + -6x = 69 + -9

Combine like terms: 9 + -9 = 0
0 + -6x = 69 + -9
-6x = 69 + -9

Combine like terms: 69 + -9 = 60
-6x = 60

Divide each side by '-6'.
x = -10

Simplifying
x = -10

See similar equations:

| 27x-9=3 | | 3a=9+22 | | 3X+73=6X-8 | | x*x+2x+x+3=x*x+5x+6 | | -2=4x+5x+7 | | 5x+20=14x+4 | | -3-5x=5x-103 | | 2(4x+2)=4(3x+1) | | -6x+2-3x=56 | | 3x+6=17+2x | | 2(3)+y=-1 | | 3x+6=17+2 | | 2(4)+y=-1 | | 5(3)+3y=-6 | | 5(6)+3y=-6 | | 3x^2+8x+5= | | 32u-8-12u=22u-6 | | 2x+10+x+7=x*x+12x+35 | | 1.2x+5=7 | | 4x(x-2)=5 | | y/7=3/14 | | =4x^3y^5 | | 4d-2=6 | | (4x-2)+(6x+6)+(7x-18)=360 | | -45=15x | | -7x-8y=-19 | | -3=-r | | 130-6x=30x+18 | | -3x-7y=-14 | | 82-6x=39x+17 | | 3x+2+3x+4=-24 | | 3+8(m-6)= |

Equations solver categories